2022
DOI: 10.1111/hae.14723
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐utility analysis of emicizumab for the treatment of severe hemophilia A patients in Canada

Abstract: Introduction: EHL FVIII products and emicizumab provide clinicians with other prophylactic options for treating hemophilia A, however, it is unclear if emicizumab is a cost-saving option. The objective of this study is to estimate the health and economic effects of using prophylactic EHL FVIII, SHL FVIII, and emicizumab in severe haemophilia A patients. Materials and Methods:A state-transition Markov model evaluated the costeffectiveness of prophylactic SHL FVIII, EHL FVIII, and emicizumab in a cohort of 2-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…9 In Germany, the economic burden of direct costs for severe HA is estimated to be 79 times higher than the mean per capita health expenditure. 10 The increasing costs for innovative therapies such as bispecific monoclonal antibodies or gene therapies 11,12 raise questions about the value of innovative treatments compared to standard treatments for decisions on health care resource allocation. Basic updated information for treatment patterns, outcomes, costs of HA, and HA-specific comorbidities stratified by age and severity is a necessary basis for value assessment of innovative therapies.…”
Section: Introductionmentioning
confidence: 99%
“…9 In Germany, the economic burden of direct costs for severe HA is estimated to be 79 times higher than the mean per capita health expenditure. 10 The increasing costs for innovative therapies such as bispecific monoclonal antibodies or gene therapies 11,12 raise questions about the value of innovative treatments compared to standard treatments for decisions on health care resource allocation. Basic updated information for treatment patterns, outcomes, costs of HA, and HA-specific comorbidities stratified by age and severity is a necessary basis for value assessment of innovative therapies.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Yu and colleagues, emicizumab prophylaxis was found to be cost-saving in Canada among patients with severe hemophilia A, dominating the standard of care prophylaxis strategy. 7 In reports by the Institute for Clinical and Economic Review, emicizumab prophylaxis was found to be cost-saving in the United States among patients with severe hemophilia A without inhibitors as well as among patients with hemophilia A with inhibitors. 8,9 It is worth noting that the baseline prevalence of bleeding events and other hemophilia A-related complications is known to be less in the moderate or mild population than in the severe population.…”
mentioning
confidence: 99%